Long-Term Settlement Scenarios for Australia: A Survey and Evaluation of Community Opinions. Issue 1 (2nd January 2022) - Bolleter, Julian; Edwards, Nicole; Freestone, Robert; Nichols, David; Oliver, Grace; Hooper, Paula
ABSTRACT: The projected long-term growth of Australia's population to over 50 million people raises significant implications for infrastructure planning and liveability. Concomitantly, support for population growth through immigration is, according to some measures, waning. This paper presents findings from a national survey, Plan My Australia, measuring support for alternative national settlement patterns for accommodating population growth. The responses favourthree possible settlement patterns – satellite cities orbiting the state capital cities, regional cities on rail links connecting the capital cities, and cities in inland regions. Policymakers should consider the findings in the context of a re-emerging national urban policy.